Anthropological Aspects of Modern Protestant Preaching (Consequences of Content Analysis) - Zhalovaga, A. S. (Ukrai͏̈ns'ke relihijeznavstvo, 2002)
In the context of changing paradigms of human thinking, secularization of social consciousness, scientific and technological and information revolution, social and environmental cataclysms, Christian preaching seeks to answer the "challenge of time", seeking and offering man such spiritual foundations of life that will help him to "find himself" in the changing in the modern world.